Investment proposals and decisions - Williams, B. R.; Scott, W. P.; Manchester Business School (London, Allen & Unwin, 1965)
This is a report on studies of the origin and outcome of investment decisions in fourteen member firms of the Centre for Business Research at the University of Manchester.
"Based on studies of ... the Centre for Business Research at the University of Manchester."
oif 29/01/2019
Loans
Keywords: Capital investments; Investment proposals